Not so Alien and Unnatural After All: Deification as Healing of Privation in Augustine's Sermons - Rosenberg, Stanley P. (Journal of religion & society. Supplement, 2018)
One typically reads that deification, or theosis, was the view held among the Eastern churches and something quite foreign to the West. In such works one finds Augustine presented as the preeminent champion of ransom theory as the way of understanding redemption. But then one reads in The City of God, “God Himself, the blessed God, who is the giver of blessedness, became partaker of our human nature, and thus offered us a short cut to participation in His own divine nature.” This sounds suspiciously like deification. Could this really be there? In fact, yes, and it is what one should expect to find in Augustine. How could others’ readings of Augustine missed this? Such have arguably been preoccupied with only one portion of Augustine’s works – his books, unduly emphasized the anti-Pelagian writings, and confused Augustine’s doctrine of redemption with later formulations of the High Middle Ages, the Reformation, and especially Protestant scholasticism. A handful of scholars have begun to strip away this misunderstanding, demonstrating that Augustine held to some form of deificatio. They have had to justify this very substantial change of interpretation on a relatively small group of texts from Augustine’s doctrinal treatises. However, more than a few sermons are also available for them to work with; when understood in context, I argue, these sermons suggest that deification is far more central to Augustine’s thought than a mere numeration of doctrinal passages suggests. Further, this article argues that Augustine’s cosmology and especially his privation theory of evil are foundational to the bishop’s broader theological development. By understanding Augustine’s view of a primal formation and a fall which corrodes the originate state which must be reformed, one realizes that the notion of deification was central to Augustine’s pastoral concerns, and that his understanding of it as providing the means for healing the corruption endemic within postlapsarian humans who retain some degree of the imago dei. This theological vision, then, is neither accidental nor incidental. Therefore, even if his use of deification is not as prevalent or developed as thoroughly as that found among the Cappadocian authors, one should understand this approach as a critical aspect of his doctrine of atonement.